The Output Decline in the Aftermath of Reform : The Cases of Bulgaria, Czechoslovakia, and Romania - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1992)
This paper analyzes the declines in economic activity experienced by Bulgaria, the Czech and Slovak Federal Republic (CSFR), and Romania in the period since the initiation of market-oriented reforms in these countries. The paper reviews developments in the three countries and empirically investigates two questions that are key to the interpretation of the output decline: First, to what extent does the output fall reflect 'structural change' (or a reallocation of resources across sectors) rather than a conventional recession? Second, to what extent have demand-side or supply-side forces been dominant in generating the output decline?.